Environmental policy and industrial innovation : strategies in Europe, the USA and Japan - Wallace, David (London : Earthscan, 1995)
Royal Institute of International Affairs. Energy and Environmental Programme
Keywords: Economic development -- Environmental aspects; Environmental policy; Industrialization -- Environmental aspects